The Effect of Triangular Vortex Generator Straight Arrangements on the NACA 0012 Airfoil Using a Smoke Generator - Trysnavirensa, Saniyya Nahda; Putro, Setyo Hariyadi Suranto; Pambudiyatno, Nyaris (SAINSTECH NUSANTARA, 2025)
Aerodynamics is a fundamental discipline in the field of aviation, as it governs the airflow around an aircraft, enabling lift generation. The design and construction of aircraft wings are critical, as they directly impact the aircraft's stability and lift efficiency. Thus, aerodynamics plays a pivotal role in the performance, functionality, and overall design of aircraft. With advancements in modern aviation, continuous improvements are being made in the design and configuration of wing models. To analyze the aerodynamic characteristics of an aircraft wing, the airflow distribution method is commonly employed, one of which includes the use of vortex generators. This study investigates the effects of adding triangular vortex generators to a NACA 0012 airfoil, utilizing the smoke generator method in a straight arrangement. The experiments were conducted in an open-circuit wind tunnel with an airflow velocity of 5 m/s. The angles of attack tested were 0°, 4°, 8°, 10°, 15°, 17°, and 20°. The vortex generators were positioned 20% of the chord length from the leading edge of the airfoil. The experimental results demonstrate that the addition of triangular vortex generators increases the distance to the furthest point of separation and enhances the transition point on the airfoil. The aerodynamic performance of the airfoil was evaluated based on the observed airflow patterns around the airfoil, which showed notable differences compared to the airfoil without vortex generators.